Commercial arbitration in cyberspace: the legal and technical requirements towards a more effective Lex Electronica Arbitralis - Kritzinger, Julian (Intellectual Property Research Unit, 2018)
Online Arbitration is an online alternative dispute resolution (OADR) process that resolves disputes without litigation outside national courts. Due to globalisation and increased e-commerce, international commercial online arbitration has become more important and it is therefore essential to look at the legal and technical requirements for a more effective international online arbitration regime or lex electronica arbitralis, specifically focused on disputes that arise from cross-border, low value e-commerce transactions for both goods and services, and especially between online businesses and consumers (B2C), but also between online businesses (B2B). The lex electronica arbitralis should lead to swift outcomes that will be able to be enforced efficiently anywhere in the world, without impairing the requirements of accountability, due process, efficiency, impartiality, independence, fairness, transparency, etc. The 'UNCITRAL Technical Notes on ODR of 2016' follows a non-binding guideline format, so there is currently no legal outline that exclusively regulates online arbitration. Due to this lacuna, the guidelines of the 'Technical Notes' and rules of traditional international commercial arbitration will have to be used as far as they accommodate online arbitration. Due to its unique features, online arbitration however needs an exclusive set of rules that will deal with its legal and technical requirements. The most comprehensive manner to have realised an online arbitration regime or lex electronica arbitralis would have been by the proposed 'UNCITRAL Draft Procedural Rules (DPR) on OADR for Cross-Border E-Commerce Transactions'. Unfortunately, since Working Group III (WG.III), who was mandated by UNCITRAL to compile the 'DPR', could not manage to reach consensus on many aspects, the 'Technical Notes' was adopted instead. The thesis will review WG.III's progress to complete the 'DPR' and how it eventually led to the adoption of the 'Technical Notes'. The 'Technical Notes' still leaves many questions and uncertainties on many of online arbitration's legal and technical requirements that will be pointed out. The thesis will indicate that these legal and technical requirements do not compose insurmountable challenges, but that UNCITRAL will have to address them when they decide to revise the 'Technical Notes' in the future or when they decide to compile a set of legal standards exclusively for online arbitration in the future. The focus will also be directed to the future of international arbitration legislation in a developing country such as SA, while a plea is made to SA lawmakers to make provision for online arbitration.